The Effect of Perfectionism and Academic Anxiety on Academic Burnout among Final-Year Students in Indonesia Completing Their Final Assignments - Desri Marianty Tanga Wila; Heru Astikasari Setya Murti; Susana Prapunoto (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Final-year undergraduate students often encounter various obstacles during the process of completing their final projects, which may lead to both academic and psychological problems. One prevalent psychological issue is academic burnout, characterized by emotional exhaustion, cynical attitudes toward academic activities, and decreased academic achievement. Perfectionism and academic anxiety are considered two important factors contributing to the emergence of this condition. This study aims to analyze and examine the effects of perfectionism and academic anxiety on academic burnout among final-year undergraduate students engaged in completing their final projects. A quantitative approach with a multiple linear regression design was employed. The research participants consisted of 355 undergraduate students in the final project stage, selected using purposive sampling. Data were collected using validated and reliable instruments, including a perfectionism scale, an academic anxiety scale, and an academic burnout scale. Data analysis was conducted using multiple regression analysis. The results indicate that perfectionism and academic anxiety simultaneously have a significant effect on academic burnout. These findings suggest that higher levels of perfectionism and academic anxiety increase students’ vulnerability to academic burnout. The results have important implications for the development of academic support services and psychological interventions to facilitate successful completion of students’ final projects.